On-farm trials identify adaptive management options for rainfed agriculture in West Africa. (June 2020) - Eldon, Jon; Baird, Graeme; Sidibeh, Saidou; Dobasin, Daniel; Rapaport, Philippe; Cheng, Weixin; Shennan, Carol
Abstract: Rainfed crop production is the primary means of food security and income generation for rural households in semi-arid West Africa, which contains a high level of agro-ecological and socio-economic heterogeneity. Official management recommendations currently focus on the use of purchased certified seed and inorganic fertilizers, but are based primarily on highly controlled on-station trials that do not capture this heterogeneity and complexity of production systems. This study established hundreds of on-farm research trials across Senegal and The Gambia to test the agronomic benefit of multiple integrated practices related to seeds, inorganic fertilizers, and locally available organic amendments. All management practice were found to reliably increase yield across both the heterogeneity of this region and the diversity of the partnering farmers, and multiple integrated practices had greater effect than the currently recommended "best" practice. These alternative practices therefore offer an immediate pragmatic replacement to the existing recommendations and demonstrate the research and extension value of supervised on-farm trials. These findings also suggest that agronomic recommendations should focus on multiple "better" options rather than singular "best" practices, and farmers encouraged to select among these options based on their individual knowledge, circumstances, and preferences. Highlights: Current management recommendations in West Africa were found to be unnecessarily narrow. Organic amendments, inorganic fertilizers, and new cultivars were all widely effective. Agro-ecological and socio-ecological conditions were poor predictors of this effectiveness. Combined practices had an additive effect and no observed response threshold. Farmers should be made aware of these options and encouraged to select individually among them.